Tajam ke Bawah, Tumpul Ke Atas: Paradoks Penegakan Hukum terhadap Koruptor - Rina Dwi Yanti Tampubolon (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Law enforcement in Indonesia continues to face various challenges, particularly in the context of eradicating corruption. The phrase "sharp downward, blunt upward" illustrates the disparity in law enforcement, where corrupt elites often receive lenient treatment while ordinary citizens committing minor offenses face severe punishment. This article analyzes the paradox using a normative-juridical and sociological approach, examining causal factors such as the lack of integrity among law enforcement officers, political interference, and vague legal norms. The study also explores how legal supremacy can be upheld fairly through systemic legal reform, strengthening of anti-corruption institutions, and community participation. By comparing several cases of corruption involving elites and legal violations by the lower class, this article highlights the importance of equality before the law as a fundamental principle of a legal state.